The Role of the Church in the Promotion of Good Governance: A Case of Kanoni Archdeaconry in North Ankole Diocese - Richard Arinaitwe (Uganda Christian University, 2023)
This study was conducted to investigate the role of the church in the promotion of good governance in Kanoni Archdeaconry. The specific objectives of the study were to investigate the role of church mobilization, participation in politics and human rights advocacy in the promotion of good governance. Data from was collected using a questionnaire and an interview guide, analyzed descriptively and presented in frequency counts and percentages. The findings show that the involvement of the church in political mobilization, elections and human rights advocacy had positive consequences on governance and service delivery. The study concluded that the church can be a good change agent regarding governance, but needs to be cautious so that politics does not rob them of their role of winning souls for Christ. Hence, the study recommended further investigation into the factors affecting church involvement in politics and how the church can balance secular governance and the promotion of the ideals of the Kingdom of God.
This is a dissertation.